Comparative Proteomic Characterization of Ventral Hippocampus in Susceptible and Resilient Rats Subjected to Chronic Unpredictable Stress - Zhang, Yani; Zhang, Xiaoling; Liu, Nuo; Ren, Siyu; Xia, Congyuan; Yang, Xiong; Lou, Yuxia; Wang, Huiqin; Zhang, Ningning; Yan, Xu; Zhang, Zhao; Zhang, Yi; et al. (Frontiers in Neuroscience, 2021)
Chronic stress is an essential factor leading to depression. However, there exist individual differences in people exposed to the same stressful stimuli; a part of people display negative psychology and behavior; the others are normal. Given the importance of individual difference, finding differentially expressed proteins in stress-resistant and stress-susceptible groups has great significance for the study of pathogenesis and treatment of depression. In this study, stress-susceptible rats and stress-resilient rats were firstly distinguished by sucrose preference test,these stress-susceptible rats also displayed depression-like behaviors in forced swimming test and open field test. Then, we employed label-free quantitative proteomic to analyze proteins in ventral hippocampus. There were 4848 proteins totally identified. Based on statistical analysis, we found 276 differentially expressed proteins. Bioinformatics analysis revealed the biological processes of these differential proteins were releated to mitochondrion organization, protein localization, coenzyme metabolic process, cerebral cortex tagential migration, vesicle-mediated transport, and so on. The KEGG pathways were mainly involved in metabolic pathways, axon guidance, autophagy, tight junction. Furthermore, we ultimately found 20 stress-susceptible proteins and 2 stress-resilient proteins. These stress-related proteins could not only be potential biomarkers for depression diagnosis, but also contribute to finding new therapeutic targets, and providing personalized medicine.